Short Communication: Mangrove forest management based on multi dimension scalling (RAP-Mforest) in Kwandang Sub-district, North Gorontalo District, Indonesia - Ramla Hartini Melo; Cecep Kusmana; Eriyatno Eriyatno; Dodik Ridho Nurrochmat (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Melo RH, Kusmana C, Eriyatno, Nurrochmat DR. 2020. Short Communication: Mangrove forest management based on multi-dimension scalling (RAP-Mforest) in Kwandang Sub-district, North Gorontalo District, Indonesia. Biodiversitas 21: 1352-1357. Management of mangrove forests is an important aspect in the effort to conserve the environment in coastal areas. Its management requires planning to ensure the sustainability of its function and benefit. This study aimed to analyze the sustainability level of the mangrove forest management in Kwandang Sub-district, North Gorontalo District, Gorontalo Province, Indonesia and to determine the factors that affected that sustainability. Data were collected through field measurement and interviews, and then analyzed using Rapid Appraisal of Mangrove Forest (Rap-Mforest) approach and Monte Carlo analysis. The results showed that mangrove management was fairly sustainable on the ecological criteria (60.43%), but less sustainable on the economic criteria (47.79%) and social criteria (42.22%). The result of leverage analysis indicated that 6 out of 20 indicators were categorized as sensitive indicators affecting the sustainability of mangrove management. These sensitive indicators should be given priority in increasing the sustainability index in the future.